Pengaruh Kemasan Penyimpanan terhadap Kadar Senyawa Non Spesifik Kemangi (Ocimum basilicum L.) pada Suhu Tertentu: The Effect of Storage Packaging on the Level of Non-Specific Compounds in Basil (Ocimum basilicum L.) at Certain Temperatures - Haani Adilah; Riski Sulistiarini; Dewi Rahmawati (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2023)
Basil (Ocimum basilicum L.) contains the most phenolic compounds among other compounds. This condition contributes to the blackening of basil leaves which can reduce the economic value and quality hence the proper storage packaging is needed. This research was conducted to determine the levels of water soluble and ethanol soluble compounds, post-storage weight changes, and qualitative analysis of phenolic compounds. Basil leaves which have been harvested and sorted then packaged in aluminum foil, banana leaves, polypropylene (PP) plastic and newspaper. The storage process is carried out at a temperature of 5-8ºC for 5 days. After storage is complete, tests are carried out to determine the levels of water-soluble and ethanol-soluble compounds, post-storage weight changes, and qualitative analysis of phenolic compounds. The use of packaging influences changes in post-storage weight of basil where banana leaves have the lowest weight loss of 6%. Meanwhile, qualitative analysis of the compounds in the treatment showed that they still contained phenolic compounds. Keywords: basil, storage packaging, compounds level Abstrak Kemangi (Ocimum basilicum L.) mengandung senyawa fenolik paling banyak di antara senyawa lainnya. Kondisi tersebut berperan kepada penghitaman daun kemangi yang dapat menurunkan nilai ekonomi dan kualitas sehingga dibutuhkan kemasan penyimpanan tepat. Penelitian ini dilakukan untuk mengetahui kadar senyawa larut air dan larut etanol, perubahan bobot pasca simpan, dan analisis kualitatif senyawa fenol. Daun kemangi yang telah dipanen dan disortasi kemudian dikemas ke dalam kemasan alumunium foil, daun pisang, plastik polipropilen (PP), dan kertas koran. Proses penyimpanan dilakukan pada suhu 5-8ºC selama 5 hari. Setelah penyimpanan selesai, dilakukan pengujian untuk mengetahui mengetahui kadar senyawa larut air dan larut etanol, perubahan bobot pasca simpan, dan analisis kualitatif senyawa fenol. Penggunaan kemasan berpengaruh terhadap perubahan bobot pasca simpan kemangi dimana daun pisang memiliki susut bobot paling rendah sebesar 6%. Sementara itu, analisis kualitatif senyawa pada perlakuan menunjukkan masih terkandung senyawa fenol. Kata Kunci: kemangi, kemasan penyimpanan, kadar senyawa